2012
DOI: 10.1007/s10802-012-9686-8
|View full text |Cite
|
Sign up to set email alerts
|

Reading Comprehension in Children with ADHD: Cognitive Underpinnings of the Centrality Deficit

Abstract: We examined reading comprehension in children with ADHD by assessing their ability to build a coherent mental representation that allows them to recall central and peripheral information. We compared children with ADHD (mean age 9.78) to word reading-matched controls (mean age 9.89) on their ability to retell a passage. We found that even though children with ADHD recalled more central than peripheral information, they showed their greatest deficit, relative to controls, on central information – a centrality d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
101
1
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(117 citation statements)
references
References 49 publications
8
101
1
6
Order By: Relevance
“…If rapid naming of objects were, in part, a marker for ADHD, than its unique relationship to reading comprehension could be explained on the basis of attentional resources. Recent research suggests that attentional deficits in children with ADHD can cause limitations in working memory that can lead to difficulties in building coherent mental representations during reading (Miller et al, 2013).…”
Section: Prediction Of Reading Comprehensionmentioning
confidence: 99%
“…If rapid naming of objects were, in part, a marker for ADHD, than its unique relationship to reading comprehension could be explained on the basis of attentional resources. Recent research suggests that attentional deficits in children with ADHD can cause limitations in working memory that can lead to difficulties in building coherent mental representations during reading (Miller et al, 2013).…”
Section: Prediction Of Reading Comprehensionmentioning
confidence: 99%
“…Others also have shown that WM is related to reading ability (Baddeley et al, 1985; Vellutino et al, 2004; Kibby and Cohen, 2008; Sesma et al, 2009; Christopher et al, 2012). Moreover, when studying children with Attention-deficit/hyperactivity disorder (ADHD), Miller et al (2013) found that poor WM contributes to their comprehension problems in that WM mediated the relationship between ADHD symptoms and the ability to recall the central ideas of the passage. WM may play a role in reading fluency as well (Baddeley et al, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest that students with ADHD were able to recall key information to perform basic comprehension of the read content 39,40 . However, since both groups presented low scores, lack of reading comprehension is evident among schoolchildren, with and without ADHD, suggesting that the current literacy methodology, in our country, does not focus on teaching strategies for reading comprehension development in the classroom.…”
mentioning
confidence: 80%